An introduction to Kodo Kyodan buddhism - Okano, Archbisho Shodo (Kodo Kyodan, 1967)
This book consists of the following many parts: the teaching of Kodo Kyodan, the faith of Kodo Kyodan, and the practice of kodo Kyodan.